Dry eye symptoms and plasma hormone levels - A pilot study - Stapleton, Fiona; Hampel, Ulrike; Badarudin, Noor Ezailina; Jalbert, Isabelle; Madigan, Michele; Golebiowski, Blanka (Elsevier, 2013)
Purpose: Dry eye symptoms are commonly reported par- ticularly in women post-menopause. This study explored the relationship between levels of plasma sex hormones and dry eye symptoms. Method: A cross-sectional, single visit study was conducted. The study involved a convenience sample of 74 subjects without ocular surface disease, including 52 females (mean age 35.3 ± 13.4years, range 18.8-70.3) and 22 males (mean age 34.2 ± 13.8years, range 20.2-75.3). Subjects completed the Dry Eye Questionnaire (DEQ5) and numerical ratings of discomfort, dryness, foreign body (FB) sensation, burning and watering. Tear osmolarity (TearLab) and volume (Phenol Red Thread) were assessed. Venous blood was collected and plasma concentrations of oestradiol (E2) and total testosterone (TT) were determined using specific enzyme-linked immunosorbent assay. Associations were examined using Pear- son’s or Spearman’s correlations, and differences between groups were assessed using independent samples t-test or Mann-Whitney U test, as appropriate. Results: Mean group E2 concentration was 65.2 ± 50.9pg/ml in females and 40.7 ± 23.8pg/ml in males; TT concentration was 0.49 ± 0.29 and 4.3 ± 1.6ng/ml respectively. Symptom reporting was higher in females (p < 0.05). Tear volume was reduced in females (p = 0.02); there was no difference in tear osmolarity. In e8 Abstracts / Contact Lens & Anterior Eye 36 (2013) e1–e15 females, increased ocular symptoms (DEQ5, dryness, FB) was asso- ciated with higher levels of E2 (p < 0.05). Higher TT in females correlated with more FB sensation and lower tear volume (p < 0.05). No association was found between tear osmolarity and hormone levels in females. There was no association between age and ocular symptoms in either males or females. Conclusions: Higher circulating levels of sex steroid hormones appear to play a role in increased symptoms of dry eye in females, but not in males. This effect does not appear to be influenced by age. Evaluation of co-related factors such as levels of free testos- terone is warranted to further explore these relationships in the pathophysiology of dry eye.